Achievement training: A re-assessment of the technique and its impact on the development of supervisory and managerial talent in Southern Africa - Martin E. Nasser (South African Journal of Business Management, 1984)
Against a scenario of an ever-increasing demand for a greater number of managers and supervisors - particularly Black talent - into the Southern African economies. this paper explores the real contribution Achievement Training has been making over the past four years. Specifically its contribution to developing managerial and supervisory talent is explored and its concomitant contribution to alleviate the critical 1:42 manager to worker ratio currently being experienced on this sub-continent.The Nasser Achievement Training Process has its origins in the work of Harvard Professor David McClelland's three-band theory. The development of this process is examined from both a construct and pedagogics point of view for purposes of critically reviewing its nature and impact.A longitudinal analysis of the results of some 2 985 prospective managers/supervisors who were exposed to the Achievement Training process reveals a number of very positive trends. The results indicate significant levels of improvement in performance on-the-job as adjudged by the immediate line managers on 10 work-related managerial supervisory dimensions.What is even more significant is that some 60% of the participants received promotions of between 1 and 4 levels during the observation period - the majority being Black. These results indicate the powerful nature of this Achievement Training process.The author argues that despite the significance of these results, this training process needs to be organic by nature. A restructuring of the contents has been proposed in order to equip even-better the latent managerial talent within the organization. Also the critical role of a well-trained Mentor has come into sharp focus as being a major facilitator in growing this managerial and supervisory talent at the fastest possible pace.
Keywords: 650